Childfree in Islamic Law Perspective of Nahdlatul Ulama - Imam Syafi'i; Tutik Hamidah; Noer Yasin; Umar Muhammad (Al-Ahkam, 2023)
Childfree is a social phenomenon that is becoming an interesting discussion today. It deserves the attention of Islamic law. Nahdlatul Ulama (NU), through the NU Bahtsul Masail Institute (LBM-NU), has issued four fatwas synonymous with the childfree phenomenon. This article aims to analyze the childfree phenomenon from the perspective of the istinbāṭ al-aḥkām method used by NU and its relevance to the four fatwas. This article is qualitative research using a normative Islamic law approach, which examines NU’s legal decisions regarding the denial of childbirth. These decisions are then analyzed to determine the meaning and method of istinbāṭ used. This article finds two things. First, the istinbāṭ al-aḥkām method used by LBM-NU is the qawlī intiqādī method. Second, from the aspect of its application, childfree can be equated in law with decisions that have been determined by LBMNU regarding child refusal, as long as the method adopted is legal. However, from the aspect of substance, where childfree is used as a principle and lifestyle, it requires a new fatwā decision, especially with the manhajī approach.